MOLECULAR EXPRESSION OF WINGLESS-TYPE MMTV INTEGRATION SITE FAMILY MEMBER 4 GENE USING Escherichia coli BL21 - Sitasiwi, Agung Janika; Artama, Wayan Tunas; Budiyanto, Agung; Dharmana, Edy (Jurnal Kedokteran Hewan, 2017)
This research was conducted to find out the Wnt4 recombinant proteins which expressed by Escherichia coli (E. coli) BL21 carrying the recombinant DNA wnt4 (E. coli transformation). Research materials were E. coli BL21 transformation and E. coli BL21 non-transformation (negative control). The expression of recombinant protein was conducted by culturing E. coli for 24 hours in Luria-Bertani (LB) media with isopropyl -D-1-thiogalactopyranoside (IPTG) induction. Recombinant protein was isolated by sonication of pellet bacteria. Protein analysis performed by 15% sodium dodecyl sulphate polyacrylamide gel electrophoresis (SDS-PAGE). The results showed that recombinant protein with a molecular weight of 33 kDa has been expressed by E. coli BL21 transformation successfully.